Design and synthesis of three-dimensional hierarchical ordered porous carbons for supercapacitors. (1st February 2015) - Zhao, Qinglan; Wang, Xianyou; Liu, Jing; Wang, Hao; Zhang, Youwei; Gao, Jiao; Lu, Qun; Zhou, Heye
Highlights: The 3D HOPCs are prepared by a facile templating method. The pore structure of the 3D HOPCs can be effectively controllable. The 3D HOPCs show exellent supercapacitive performances. The high specific capacitance of 247 F g −1 is achieved. Abstract: Three-dimensional hierarchical ordered porous carbons (3D HOPCs) have been successfully prepared through templating method using silica sphere nano-array as a hard template, triblock copolymer P123 as a soft template and sucrose as a carbon source, and used as the electrode materials for supercapacitors. The structure, morphology and physicochemical properties of the as-prepared 3D HOPCs are characterized by nitrogen adsorption–desorption isotherm, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and cyclic voltammetry (CV), galvanostatic charge–discharge (GCD) tests, and cycle life measurements. The results show that the 3D HOPCs possess well-interconnected 3D hierarchical ordered porous structure. Especially, the 3D HOPC-80, of which the pore size is 4.01 nm, shows the specific surface area of 1182 m 2 g −1 and a specific capacitance of 247 F g −1 at the current density of 1 A g −1 . Besides, the supercapacitors based on 3D HOPCs exhibit excellent rate performance, high energy densities of 7.5 W h kg −1 and 5.8 W h kg −1 at the power densities of 500 W kg −1 and 10000 W kg −1, respectively. Moreover, the supercapacitors using 3D HOPCs as electrode materials hold high capacitance retentions over 91% even after 10000 cycles.